Factors affecting high school students’ academic performance: a case study in Vietnam - Hung, Le Thai; Thuy, Dang Thi Thanh; Thien, Tran Van (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigates the factors that influence academic achievement among Vietnamese high school students, with an emphasis on a case study conducted at a specific school. To identify key determinants of students’ academic success, a quantitative survey comprising questionnaires was distributed to 438 high school students. Exploratory factor analysis (EFA) was utilized, followed by Pearson correlation coefficient and regression analysis to assess the relationships between independent variables (school-related and student-related factors) and the dependent variable (student performance). The data show that teacher competency has the greatest influence on students’ academic success, closely followed by students’ learning techniques. In addition, student motivation has a significant impact on their success. The results underscore the importance of a supportive home and school environment in fostering student achievement. The results highlight the need for enhanced teacher training to improve educational quality. It is also essential to promote students’ effective learning techniques, and ensure consistency in their study. This research contributes to a deeper understanding of the complex interplay of factors impacting academic performance and offers insights for educators and policymakers aiming to enhance educational outcomes in Vietnam. Recommendations for future research and practical interventions are discussed.